2021
DOI: 10.1039/d1ra02854e
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the metal retention role in the antibacterial behavior of montmorillonite and cellulose tissue-supported copper and silver nanoparticles

Abstract: The role of the retention strength of Cu0 and Ag0 nanoparticles on the induced antibacterial properties of montmorillonite and cellulose-supported polyol dendrimer against Escherichia coli DH5α and Bacillus subtilis 168 was comparatively investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…1 H-NMR (300 MHz, D 2 O): δ 7.49 (s, 8H), 4.91 (d, J = 1.2 Hz, 4H), 4.79 (s, 16H), 3.89 (dd, J = 10.5, 5.7 Hz, 48H), 3.78 (dd, J = 12.5, 6.9 Hz, 1H), 3.69 (dd, J = 12.4, 3.5 Hz, 1H), 3.58 (dd, J = 16.9, 7.6 Hz, 1H), 3.51-3.45 (m, 84H); 13 Metal-entrapment in glycodendrimer. The cation-loaded dendrimers were obtained by adding 15 mg of the glycodendrimer to 10 mL aqueous solutions of either 0.0005 mol/L Cu(OAc) 2 or 0.0005 mol/L AgNO 3 under vigorous stirring at room temperature for 2 h according to Noori et al with minor modifications [35]. Then, to the obtained cation-containing glycodendrimers (11-Cu 2+ or 11-Ag + ) were added 10 mL of 0.001 mol/L NaBH 4 solution and the mixtures were stirred for 6 h at room temperature to afford zero-valent CuNP-loaded glycodendrimer (11-Cu 0 ) and AgNP-loaded glycodendrimer (11-Ag 0 ).…”
Section: Synthesis Of Peracetylated Glycodendrimer (10)mentioning
confidence: 99%
See 1 more Smart Citation
“…1 H-NMR (300 MHz, D 2 O): δ 7.49 (s, 8H), 4.91 (d, J = 1.2 Hz, 4H), 4.79 (s, 16H), 3.89 (dd, J = 10.5, 5.7 Hz, 48H), 3.78 (dd, J = 12.5, 6.9 Hz, 1H), 3.69 (dd, J = 12.4, 3.5 Hz, 1H), 3.58 (dd, J = 16.9, 7.6 Hz, 1H), 3.51-3.45 (m, 84H); 13 Metal-entrapment in glycodendrimer. The cation-loaded dendrimers were obtained by adding 15 mg of the glycodendrimer to 10 mL aqueous solutions of either 0.0005 mol/L Cu(OAc) 2 or 0.0005 mol/L AgNO 3 under vigorous stirring at room temperature for 2 h according to Noori et al with minor modifications [35]. Then, to the obtained cation-containing glycodendrimers (11-Cu 2+ or 11-Ag + ) were added 10 mL of 0.001 mol/L NaBH 4 solution and the mixtures were stirred for 6 h at room temperature to afford zero-valent CuNP-loaded glycodendrimer (11-Cu 0 ) and AgNP-loaded glycodendrimer (11-Ag 0 ).…”
Section: Synthesis Of Peracetylated Glycodendrimer (10)mentioning
confidence: 99%
“…Other biopolymers, suitable as carriers for silver and copper are already used in the laboratory to control Gram-negative bacterial proliferation. It was previously shown [35,36] that zero-valent silver and copper hosted by carboxymethyl derivatives are bactericides against non-pathogenic Gram-negative bacteria. We propose now an investigation of the bactericidal activity of glycodendrimers unloaded and loaded zero-valent metals.…”
Section: Introductionmentioning
confidence: 99%
“…On account of that, metal ions are adsorbed on the cell wall by electrostatic attraction, causing shrinkage of the cytoplasm membrane or detachment of the cell wall, resulting in inactivation and inhibition in cell processes [17,41]. In this scenario, strong metal retention capacity of the solid support improves antimicrobial activity, which could be achieved by tailoring weak hydroxyl groups of polymer-metal interaction, and an optimum amount of metal-loaded polymer onto MMT substrate [42]. The adsorption of bacteria (Coliphages T1 and T7 of E. coli) on MMT clay was investigated for the first time by Schiffenbauer M. and Stotzky G. [43].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an innovative approach of integration of antibacterial nanoparticles into monolithic nanofiber scaffolds has been investigated due to its advantages of cost-effectiveness, quick response, and structural simplicity. Metal (Cu, Au), metallic oxide (Fe 3 O 4 , glass particles), , or extracted bioparticles such as cellulose nanocrystal particles , incorporated into monolithic fiber scaffolds for controlled drug delivery has aroused great interest. For example, silver nanoparticles were incorporated into cotton fibers, which demonstrated great antibacterial activities. Silica nanoparticles encapsulating fluorescein and rhodamine B were integrated into poly­(lactic- co -glycolic acid) (PLGA) fibrous scaffolds, demonstrating controlled release of drugs. Results from Xing’s study showed lysophosphatidic acid and zinc oxide nanoparticles were successfully incorporated into nanofibers .…”
Section: Introductionmentioning
confidence: 99%